Analisis Hasil Belajar Siswa Kelas V SD Pada Mata Pelajaran IPAS Dalam Metode Pembelajaran Small Group Discussion - Putri Maharani; Sinta Andayani; Sahda Aqila Nisa; Riska Ayuk Cahyani; Fina Fakhriyah; Nur Fajrie (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine how the learning method of small group discussion on the learning outcomes of grade V students on IPAS learning materials. Seeing the many kinds of learning methods that have been used in this learning process, the focus of study in this study is to answer whether the small group discussion learning method can improve student learning outcomes in IPAS lessons. This research is a qualitative method where the author uses a phenomenological approach. The subjects in this study are teachers and children in elementary schools. The subject is a teacher who teaches IPAS subjects in grade 5. As for the subject of elementary school children, they are high school students who are grade 5 students. The Small Group Discussion method in IPAS learning at SD 4 Gondangmanis has been positively proven. Students showed high interest, increased understanding of the material and were able to work well together. This method helps students receive and understand complex material, as well as develop critical and analytical thinking skills. Strategies used include fair division of groups and the use of roles within groups. The positive impacts seen were the development of collaborative skills, increased student engagement, improved critical thinking, and better understanding of concepts. Teachers' motivating factors in applying this method were reducing students' selfishness, encouraging their courage in expressing opinions, and improving students' ability to discuss and teach their peers. The challenges faced were students who did not want to make friends with other students and differences of opinion within the group. Teachers overcame these challenges by providing an understanding of the importance of friendship and teaching how to manage differences of opinion.